BAZNAS and the Constitutional Legitimacy of the National Zakat System: A Sharia Economics Perspective - Muhaimin Muhaimin; Fatmawati Fatmawati; Suhendra Suhendra; Yessi Fitri; Ela Patriana; Bahrul Yaman (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This research examines the constitutional legitimacy of the national zakat system through the role of the National Amil Zakat Agency (BAZNAS) after the 2023 Constitutional Court decision and explores the challenges and opportunities for digitalization integration in zakat governance to support the Sustainable Development Goals (SDGs). The method used is Systematic Literature Review (SLR) with PRISMA guidelines. Data sourced from the Scopus database using strategic keywords related to zakat, resulting in 209 articles which were then filtered into 41 studies that were worth analysis. A selection process ensures transparency and consistency, while thematic analysis focuses on issues of legal legitimacy, zakat governance, and digital transformation. The results of the analysis revealed three main findings. First, the constitutional legitimacy of BAZNAS strengthens the integration of zakat into national law while expanding its socio-economic function. Second, the digitization of zakat, especially through e-zakat and blockchain technology, has significant potential to increase efficiency, transparency, and public participation, although it still faces obstacles related to digital literacy and public trust. Third, zakat has been proven to contribute significantly to poverty alleviation and the achievement of the SDGs; However, its long-term effectiveness still requires further validation through more in-depth and cross-country empirical studies. This research emphasizes the importance of strengthening zakat governance based on sharia principles that are integrated with state law, while encouraging the adoption of modern technology. Future research needs to be directed at cross-border comparison models, the development of innovative digital platforms, as well as multidisciplinary approaches that synergize law, economics, and technology to ensure zakat remains relevant in the context of globalization and future socio-economic challenges. Penelitian ini bertujuan menelaah legitimasi konstitusional sistem zakat nasional melalui peran Badan Amil Zakat Nasional (BAZNAS) pasca putusan Mahkamah Konstitusi tahun 2023, sekaligus mengeksplorasi tantangan dan peluang integrasi digitalisasi dalam tata kelola zakat untuk mendukung tujuan pembangunan berkelanjutan. Metodologi penelitian menggunakan Systematic Literature Review (SLR) dengan pedoman PRISMA. Data diperoleh dari basis Scopus menggunakan kata kunci strategis terkait zakat, menghasilkan 209 artikel yang kemudian disaring menjadi 41 studi layak analisis. Proses seleksi ketat memastikan transparansi dan konsistensi, sementara analisis tematik difokuskan pada isu legitimasi hukum, governance zakat, dan transformasi digital. Hasil analisis menunjukkan tiga temuan utama. Pertama, legitimasi konstitusional BAZNAS memperkuat integrasi zakat dalam hukum nasional sekaligus memperluas fungsi sosial-ekonomi zakat. Kedua, digitalisasi zakat, khususnya melalui e-zakat dan teknologi blockchain, berpotensi meningkatkan efisiensi, transparansi, serta partisipasi masyarakat, meski masih menghadapi kendala literasi digital dan kepercayaan publik. Ketiga, zakat terbukti berkontribusi signifikan pada pengentasan kemiskinan dan pencapaian Sustainable Development Goals (SDGs), namun efektivitas jangka panjangnya masih perlu diukur melalui studi empiris yang lebih mendalam dan lintas negara. Penelitian ini menegaskan pentingnya penguatan governance zakat berbasis prinsip syariah yang terintegrasi dengan hukum negara, sekaligus mendorong adopsi teknologi modern. Ke depan, riset perlu diarahkan pada model komparatif antarnegara, pengembangan platform digital inovatif, serta pendekatan multidisipliner yang menyinergikan hukum, ekonomi, dan teknologi untuk memastikan zakat tetap relevan dalam konteks globalisasi dan tantangan sosial-ekonomi masa depan